2023
DOI: 10.1093/femsre/fuad007
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of plant metabolism by pathogen effectors: more than just food

Abstract: To successfully infect plants, pathogens secrete effector proteins to the plant apoplast or inside plant cells, where they suppress plant immunity or interfere with other cellular processes to facilitate infection. Plant metabolism is crucial for most cellular processes and plays a key role in defense against pathogens, making it a major target for pathogen effectors. Effector proteins manipulate host metabolism to provide the pathogen with nutrients or to indirectly suppress plant chemical defense responses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 196 publications
0
6
0
Order By: Relevance
“…In this case, a search for co-expressed genes associated with a state of susceptibility was performed in addition to the central genes explained above. For example, different authors have proposed that pathogens can manipulate host proteins to export nutrients to the apoplast [ 49 , 50 ]. Therefore, a search was performed for genes related to nutrient transportation, such as sugar and sulfur transporters.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, a search for co-expressed genes associated with a state of susceptibility was performed in addition to the central genes explained above. For example, different authors have proposed that pathogens can manipulate host proteins to export nutrients to the apoplast [ 49 , 50 ]. Therefore, a search was performed for genes related to nutrient transportation, such as sugar and sulfur transporters.…”
Section: Resultsmentioning
confidence: 99%
“…Research on effector proteins secreted by plant pathogens over the past years has led to the conclusion that effectors are often multifunctional proteins and may have several different virulence targets in plant cells (Macho, 2016; Toruño et al ., 2016; Cai et al ., 2023), altogether contributing to the promotion of pathogen proliferation. Our research has shown that the T3E protein RipI is able to promote GABA accumulation in plant tissues (Xian et al ., 2020) and to suppress specific PAMP‐triggered immune responses, including ROS burst (Figs 1, 2) and the activation of defence‐related genes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A powerful tool to achieve such manipulation is the secretion of proteins directly inside plant cells using a type‐III secretion system. These proteins, termed type‐III effectors (T3Es), have been shown to target numerous plant functions, including immunity, metabolism, or development (Macho, 2016; Toruño et al ., 2016; Cai et al ., 2023). Importantly, T3Es are multifunctional proteins, able to target different plant processes simultaneously (Macho, 2016; Toruño et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this gene was down-regulated in a tolerant inbred line at early stages of infection with the fungus S. sclerotiorum in sunflower, suggesting a common functional role in pathogen-associated molecular pattern (PAMP)triggered immunity [55]. Several authors have identified modulation of primary metabolic pathways during the defense response, although the specific players in each species remain to be elucidated [56][57][58].…”
Section: Discussionmentioning
confidence: 99%